INDUSTRIAL PRODUCTION EQUIPMENT MAINTENANCE SYSTEMS - Dzērve, Nauris; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
In today's widely competing food production market, the cost of production, the time of preparation for work and the optimal use of funds are particularly important for the competition in the existing market. A successful and growing manufacturing company is based on the continuous development and optimization of the production process, in order to minimize product modulation, production and delivery times, and provide high quality products to customers.